Technology Acceptance Model (TAM) as Factors of Online Vegetable Purchasing Decision - Avivah Rahmaningtyas; Nanang Kusuma Mawardi; Ignatius Suprih Sudrajat (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2022)
The growth of e-commerce and vegetable consumption become a good opportunities for vegetable sellers to expand their business online. Understanding how consumers perceive the two elements of TAM is important as it will help vegetable sellers formulate a strategy that applies specifically to their online store. In this study, Structural Equation Modeling - Partial Least Squares (SEM-PLS) is used to analyze the data. The independent variables in this study were perceived usefulness (PU) and perceived ease of use (PEOU), meanwhile the dependent variable was purchase decision (KP). This study have met the criteria of validity and reliability. The result of this research is two component of TAM significantly affecting vegetable purchasing decision in online stores. Using significance level at 0.05, t-statistic for PEOU is 3,627 which is greater than 1.960, meanwhile t-statistic for PU is 5,394 which is greater than 1.960. The owner business of vegetable in online store should develop their platform to help consumer feel more convenient and efficient while purchasing the product online.